Sołectwo jako jednostka pomocnicza gminy: Office of the village leader as a unit community - Śwital, Paweł (Management and Administration Journal, 2021)
The article presents the issues of the auxiliary unit which is the parish municipalities. The purpose of this article is to present the basic regulations from the scope of village councils, village councils authorities, the statute as a basis for action villages, as well as the hamlet fund. The author analyzes the law on the basis of dogmatic methods - legal.